The Moral Values in the Upin Ipin Animated Film Episode "The Beginning of Ramadhan" (Gamson and Modigliani Framing Model Analysis) - Andriana, Niar; wandi, wandi (Palakka : Media and Islamic Communication, 2022)
Film is one of mass media that people are most interested in because it delivers picture and sound simultaneously. It also has become the means of educating as well as means of propaganda to spread the cultural values among society. One of film that educating and having moral values is animated film Upin and Ipin. Hence, this research objectives is to analyze the moral values in Upin and Ipin on episode "The Beginning of Ramadhan" and this research is analyzed using framing model of Gamson and Modigliani. The findings report that the moral values in Upin and Ipin animated film episode "The Beginning of Ramadhan" describes positive issues that has moral values in the story which teaches human being to be trustworthy and responsible with the given work and always be honest as well as to have good deeds and words.